An integrative morpho-molecular approach in malignant ectomesenchymoma diagnosis: report of a new paediatric case and a review of the literature - Pellegrino, Francesco; Tirtei, Elisa; Divincenzo, Federico; Campello, Anna; Rubino, Carlotta; Augustoni, Elisabetta; Linari, Alessandra; Asaftei, Sebastian Dorin; Fagioli, Franca (Frontiers in Oncology, 2024)
Malignant ectomesenchymoma (MEM) is a soft tissue tumour, consisting of both malignant neuroectodermal elements and one or more mesenchymal elements.Here we describe the case of a 6-months-old male, previously treated in another hospital for abdominal rhabdomyosarcoma (RMS). Histological re-examination demonstrated that the tumour had mesenchymal and neuroectodermal elements components, with a new diagnosis of abdominalpelvic MEM. A Next-Generation Sequencing (NGS) analysis was performed on a surgical tumour specimen and revealed the presence of a somatic mutation, already reported in MEM cases. We carried out a review of the literature and we found 33 new cases of MEM since the last review. We reported the clinic-pathologic features of new cases of MEM, highlighting the role of molecular studies in supporting the diagnosis of this ambiguous tumours.We promote the importance of a diagnosis based on an integrative morpho-molecular approach, that routinely include molecular analysis and the use of bioinformatic mutation detection tools, to support diagnostic and therapeutical queries and to highlight tumour biology and behaviour.